Outdoor Thermal Comfort Optimization through Vegetation Parameterization: Species and Tree Layout - Sayad, Bouthaina; Alkama, Djamel; Rebhi, Redha; Menni, Younes; Ahmad, Hijaz; İnç, Mustafa; Elnaggar, Ashraf Y. (Mdpi, 2021)
The optimization of outdoor thermal comfort has become the keystone to guarantee the healthy and comfortable use of outdoor spaces. This study aims to optimize the outdoor thermal comfort through vegetation parameterization in a boulevard located in Guelma city, Algeria during summertime. However, two main parameters were investigated, species and tree layout, through a numerical simulation. We first collected microclimate data of a sunny summer day. Second, we used real microclimate data in different simulations using the Envi-met atmospheric model. The findings reveal that Ficus Nitida is the most significant species to intercept solar radiation and provide shade over the day in Souidani Boudjemaa Boulevard, with a maximum reduction of T-a = 0.3 degrees C and UTCI = 2.6 degrees C at 13:00 p.m. Tree layout is a determining parameter in the creation of shaded paths, based on the quality of the shadows cast by the trees, namely, their size. Thereby, planting the washingtonia palm trees along the center of the boulevard is the best option to maximize the shaded area within the boulevard, with maximum reduction of T-a = 1.8 degrees C and UTCI = 3.5 degrees C at 16:00 p.m.
Keywords: outdoor thermal comfort; vegetation parameterization; tree species; tree layout; summertime; optimization; numerical simulation